A história da Comissão Parlamentar de Inquérito da União Nacional dos Estudantes CPI da UNE (1964) - Botelho, William Marcos (2017)
This dissertation aims to describe and analyze the documentation of the Parliamentary Commission of Inquiry (CPI) of the National Union of Students (UNE) showing its constitution, organization, main themes, and the developments of that fact to the Brazilian student movement. The CPI was created by the Resolution number 25, published in the Diário do Congresso Nacional (National Congress Diary) of July, the 13th, 1963, page 4329, having the interest of investigating the application of public resources foreseen by the budget of the Union in the period between 1962 and 1963 and that were used for the student activities linked to the UNE. The research runs through the process until final approval of the report. The temporal cut of the research is from the year 1962, when the UNE happens to be accused as subversive by the Congress and the vehicles of communication, to the year 1964 when the process is closed. The CPI does not prove the diversion of funds, but, in fact, consolidates itself as a vehicle for the dismantling of the student body, based on clashes between students, teachers and congressmen. The main sources were the documents produced during the process, all found in the Chamber of Deputies